An optofluidic antenna for enhancing the sensitivity of single-emitter measurements - Morales-Inostroza, Luis; Folz, Julian; Kühnemuth, Ralf; Felekyan, Suren; Wieser, Franz Ferdinand; Seidel, Claus A.M.; Götzinger, Stephan; Sandoghdar, Vahid (Nature Communications, 2024)
Many single-molecule investigations are performed in fluidic environments, for example, to avoid unwanted consequences of contact with surfaces. Diffusion of molecules in this arrangement limits the observation time and the number of collected photons, thus, compromising studies of processes with fast or slow dynamics. Here, we introduce a planar optofluidic antenna (OFA), which enhances the fluorescence signal from molecules by about 5 times per passage, leads to about 7-fold more frequent returns to the observation volume, and significantly lengthens the diffusion time within one passage. We use single-molecule multi-parameter fluorescence detection (sm-MFD), fluorescence correlation spectroscopy (FCS) and Förster resonance energy transfer (FRET) measurements to characterize our OFAs. The antenna advantages are showcased by examining both the slow (ms) and fast (50 μs) dynamics of DNA four-way (Holliday) junctions with real-time resolution. The FRET trajectories provide evidence for the absence of an intermediate conformational state and introduce an upper bound for its lifetime. The ease of implementation and compatibility with various microscopy modalities make OFAs broadly applicable to a diverse range of studies.
CRIS-Team Scopus Importer:2024-03-29

An ultrasmall mode volume cantilever-based Fabry-Pérot microcavity - Kelkar, Hrishikesh; Wang, Daqing; Hoffmann, Björn; Christiansen, Silke; Götzinger, Stephan; Sandoghdar, Vahid (CLEO: QELS - Fundamental Science, CLEO_QELS 2015, 2015)
A tunable Fabry-Pérot microcavity consisting of a 2.6 μm curvature mirror and 0.4 numerical aperture is fabricated. We study the effect of a nanoparticle on the cavity modes and discuss the coupling of single molecules. © OSA 2015.

A single molecule as a high-fidelity photon gun for producing intensity-squeezed light - Chu, Xiao Liu; Götzinger, Stephan; Sandoghdar, Vahid (Optics InfoBase Conference Papers, 2017)
CRIS-Team Scopus Importer:2023-03-27

A single molecule as a high-fidelity photon gun for producing intensity-squeezed light - Chu, Xiao-Liu; Götzinger, Stephan; Sandoghdar, Vahid (Nature Photonics, 2017)
A two-level atom cannot emit more than one photon at a time. As early as the 1980s, this quantum feature was identified as a gateway to € single-photon sources', where a regular excitation sequence would create a stream of light particles with photon number fluctuations below the shot noise. Such an intensity-squeezed beam of light would be desirable for a range of applications, such as quantum imaging, sensing, enhanced precision measurements and information processing. However, experimental realizations of these sources have been hindered by large losses caused by low photon-collection efficiencies and photophysical shortcomings. By using a planar metallodielectric antenna applied to an organic molecule, we demonstrate the most regular stream of single photons reported to date. The measured intensity fluctuations were limited by our detection efficiency and amounted to 2.2€...dB squeezing.
CRIS-Team Scopus Importer:2023-03-27

A sub-λ3 mode volume cantilever-based Fabry-Pérot microcavity - Kelkar, Hrishikesh; Wang, Daqing; Hoffmann, Björn; Christiansen, Silke; Götzinger, Stephan; Sandoghdar, Vahid (Optics InfoBase Conference Papers, 2014)
CRIS-Team Scopus Importer:2023-03-07

Chip-based all-optical control of single molecules coherently coupled to a nanoguide - Tuerschmann, Pierre; Rotenberg, Nir; Renger, Jan; Harder, Irina; Lohse, Olga; Utikal, Tobias; Götzinger, Stephan; Sandoghdar, Vahid (Nano Letters, 2017)
The feasibility of many proposals in nanoquantum-optics depends on the efficient coupling of photons to individual quantum emitters, the possibility to control this interaction on demand, and the scalability of the experimental platform. To address these issues, we report on chip-based systems made of one-dimensional subwavelength dielectric waveguides (nanoguides) and polycyclic aromatic hydrocarbon molecules. We discuss the design and fabrication requirements, present data on extinction spectroscopy of single molecules coupled to a nanoguide mode, and show how an external optical beam can switch the propagation of light via a nonlinear optical process. The presented architecture paves the way for the investigation of many-body phenomena and polaritonic states and can be readily extended to more complex geometries for the realization of quantum integrated photonic circuits.
CRIS-Team Scopus Importer:2023-03-27
Keywords: evanescent coupling; hybrid systems; nonlinear optics; On-chip single photon source; quantum optics; subwavelength nanoguides

Coherent coupling of a single molecule to a scanning Fabry-Pe´rot microcavity - Wang, Daqing; Kelkar, Hrishikesh; Martin-Cano, Diego; Utikal, Tobias; Götzinger, Stephan; Sandoghdar, Vahid (Optics InfoBase Conference Papers, 2017)
CRIS-Team Scopus Importer:2023-03-27

Coherent coupling of a single molecule to a scanning Fabry-Perot microcavity - Wang, Daqing; Kelkar, Hrishikesh; Martin-Cano, Diego; Utikal, Tobias; Götzinger, Stephan; Sandoghdar, Vahid (Physical Review X, 2017)
Organic dye molecules have been used in a great number of scientific and technological applications, buttheir wider use in quantum optics has been hampered by transitions to short-lived vibrational levels, whichlimit their coherence properties. To remedy this, one can take advantage of optical resonators. Here, wepresent the first results on coherent molecule-resonator coupling, where a single polycyclic aromatichydrocarbon molecule extinguishes 38% of the light entering a microcavity at liquid helium temperature.We also demonstrate fourfold improvement of single-molecule stimulated emission compared to free-spacefocusing and take first steps for coherent mechanical manipulation of the molecular transition. Ourapproach of coupling molecules to an open and tunable microcavity with a very low mode volume andmoderately low quality factors of the order of 103 paves the way for the realization of nonlinear andcollective quantum optical effects.
CRIS-Team Scopus Importer:2023-03-27
Keywords: Atomic and molecular physics; Optics; Physical chemistry

Coherent coupling of single molecules to a chip-based optical circuit - Rattenbacher, Dominik; Shkarin, Alexey; Renger, Jan; Utikal, Tobias; Götzinger, Stephan; Sandoghdar, Vahid (Optics InfoBase Conference Papers, 2019)
We present the coherent coupling of single dye molecules to subwavelength waveguides (nanoguides) and microresonators made of TiO2 on a chip. Integrated electrodes allow us to tune several molecules into resonance via the Stark effect.
CRIS-Team Scopus Importer:2019-07-09

Coherent coupling of single molecules to microresonators - Shkarin, Alexey; Rattenbacher, Dominik; Renger, Jan; Utikal, Tobias; Götzinger, Stephan; Sandoghdar, Vahid (2019 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2019, 2019)
Many interesting proposals in quantum optics and light-matter interaction rely on having multiple quantum emitters well-coupled to a single mode of light. Of particular interest are cases where several identical emitters couple to a one-dimensional (1D) photonic medium. Recently, we presented such a system by evanescent coupling of organic dye molecules to the same guided mode of an on-chip subwavelength waveguide [1]. While this coupling allowed us to demonstrate up to 7.5% transmission extinction of the propagating light by a single molecule, it is still not sufficient for achieving higher-order effects such as photon-mediated interaction of multiple emitters coupled to the same waveguide.
CRIS-Team Scopus Importer:2019-11-15

Coherent coupling of single molecules to on-chip ring resonators - Rattenbacher, Dominik; Shkarin, Alexey; Renger, Jan; Utikal, Tobias; Götzinger, Stephan; Sandoghdar, Vahid (New Journal of Physics, 2019)
We report on cryogenic coupling of organic molecules to ring microresonators obtained by looping subwavelength waveguides (nanoguides). We discuss fabrication and characterization of the chip-based nanophotonic elements which yield a resonator finesse in the order of 20 when covered by molecular crystals. Our observed extinction dips from single molecules reach 22%, consistent with an expected enhancement factor of up to 11 for the molecular emission into the nanoguide. Future efforts will aim at efficient coupling of a handful of molecules via their interaction with a ring microresonator mode, setting the ground for the realization of quantum optical cooperative effects.
CRIS-Team WoS Importer:2019-07-19

Coherent interaction of light with a single molecule and a plasmonic nanoparticle - Zirkelbach, Johannes; Türschmann, Pierre; Renger, Jan; Utikal, Tobias; Götzinger, Stephan; Sandoghdar, Vahid (Optics InfoBase Conference Papers, 2019)
We demonstrate partial cloaking of a gold nanoparticle by a single organic molecule as a result of their coherent interaction with a monochromatic laser beam at cryogenic temperatures. Spectral and fluorescence lifetime analyses are presented.
CRIS-Team Scopus Importer:2019-07-09

Coherent nonlinear optics of quantum emitters in nanophotonic waveguides - Türschmann, Pierre; Le Jeannic, Hanna; Simonsen, Signe F.; Haakh, Harald R.; Götzinger, Stephan; Sandoghdar, Vahid; Lodahl, Peter; Rotenberg, Nir (Nanophotonics, 2019)
Coherent quantum optics, where the phase of a photon is not scrambled as it interacts with an emitter, lies at the heart of many quantum optical effects and emerging technologies. Solid-state emitters coupled to nanophotonic waveguides are a promising platform for quantum devices, as this element can be integrated into complex photonic chips. Yet, preserving the full coherence properties of the coupled emitter-waveguide system is challenging because of the complex and dynamic electromagnetic landscape found in the solid state. Here, we review progress toward coherent light-matter interactions with solid-state quantum emitters coupled to nanophotonic waveguides. We first lay down the theoretical foundation for coherent and nonlinear light-matter interactions of a two-level system in a quasi-one-dimensional system, and then benchmark experimental realizations. We discuss higher order nonlinearities that arise as a result of the addition of photons of different frequencies, more complex energy level schemes of the emitters, and the coupling of multiple emitters via a shared photonic mode. Throughout, we highlight protocols for applications and novel effects that are based on these coherent interactions, the steps taken toward their realization, and the challenges that remain to be overcome.
CRIS-Team Scopus Importer:2019-09-24
Keywords: nonlinear optics; quantum photonics; solid-state emitters; waveguides

Collecting and Manipulating Single Photons with Near-Unity Efficiency - Götzinger, Stephan (2020 European Conference on Optical Communications, ECOC 2020, 2020)
In this tutorial I will first review various approaches which have been employed to efficiently collect single photons from a single emitter. In the second part I will discuss experiments where a single molecule provides an optical nonlinearity strong enough to manipulate single photons.
CRIS-Team Scopus Importer:2021-04-19

Comparison of back focal plane imaging of nitrogen vacancy centers in nanodiamond and core-shell CdSe/CdS quantum dots - Christinck, J.; Rodiek, B.; López, M.; Georgieva, H.; Hofer, H.; Götzinger, Stephan; Kück, S. (Journal of Physics: Conference Series, 2022)
We report on the characterization of the angular-dependent emission of two different single-photon emitters based on nitrogen-vacancy centers in nanodiamond and on core-shell CdSe/CdS quantum dot nanoparticles. The emitters were characterized in a confocal microscope setup by spectroscopy and Hanbury-Brown and Twiss interferometry. The angular-dependent emission is measured using a back focal plane imaging technique. A theoretical model of the angular emission patterns of the 2D dipoles of the emitters is developed to determine their orientation. Experiment and model agree well with each other.
CRIS-Team Scopus Importer:2022-02-11

Controlled generation of intrinsic near-infrared color centers in 4H-SiC via proton irradiation and annealing - Rühl, Maximilian; Ott, Christian; Götzinger, Stephan; Krieger, Michael; Weber, Heiko B. (Applied Physics Letters, 2018)
We report on the generation and annihilation of color centers in 4H silicon carbide (SiC) by proton irradiation and subsequent annealing. Using low-temperature photoluminescence (PL), we study the transformation of PL spectra for different proton doses and annealing temperatures. Among well reported defect signatures, we observe omnipresent but not yet identified PL signatures consisting of three sharp and temperature stable lines (denoted TS1,2,3) at 768.8 nm, 812.0 nm, and 813.3 nm. These lines show a strong correlation throughout all measurement parameters, suggesting that they belong to the same microscopic defect. Further, a clear dependence of the TS1,2,3 line intensities on the initial implantation dose is observed after annealing, indicating that the underlying defect is related to implantation induced intrinsic defects. The overall data suggest a sequential defect transformation: proton irradiation initially generates isolated silicon vacancies which are transformed into antisite vacancy complexes which are, in turn, transformed into presumably intrinsic-related defects, showing up as TS1,2,3 PL lines. We present recipes for the controlled generation of these color center
Keywords: Farbzentren

Efficient on-chip interface for many-body quantum optics with single molecules - Türschmann, Pierre; Rotenberg, Nir; Renger, Jan; Utikal, Tobias; Götzinger, Stephan; Sandoghdar, Vahid (Optics InfoBase Conference Papers, 2017)
CRIS-Team Scopus Importer:2023-03-27

Experimental realization of an absolute single-photon source based on a single nitrogen vacancy center in a nanodiamond - Rodiek, Beatrice; Lopez, Marco; Hofer, Helmuth; Porrovecchio, Geiland; Smid, Marek; Chu, Xiao-Liu; Götzinger, Stephan; Sandoghdar, Vahid; Lindner, Sarah; Becher, Christoph; Kuck, Stefan (Optica, 2017)
We report on the experimental realization of an absolute single-photon source based on a single nitrogen vacancy (NV) center in a nanodiamond at room temperature and on the calculation of its absolute spectral photon flux from experimental data. The single-photon source was calibrated with respect to its photon flux and its spectral photon rate density. The photon flux was measured with a low-noise silicon photodiode traceable to the primary standard for optical flux, taking into account the absolute spectral power distribution using a calibrated spectroradiometer. The optical radiant flux is adjustable from 55 fW, which is almost the lowest detection limit for the silicon photodiode, and 75 fW, which is the saturation power of the NV center. These fluxes correspond to total photon flux rates between 190,000 photons per second and 260,000 photons per second, respectively. The single-photon emission purity is indicated by a g(2)(0) value, which is between 0.10 and 0.23, depending on the excitation power. To our knowledge, this is the first single-photon source absolutely calibrated with respect to its absolute optical radiant flux and spectral power distribution, traceable to the corresponding national standards via an unbroken traceability chain. The prospects for its application, e.g., for the detection efficiency calibration of single-photon detectors as well as for use as a standard photon source in the low photon flux regime, are promising.
CRIS-Team Scopus Importer:2023-03-27
Keywords: Metrology; Photon statistics; Radiometry; Sources

Fabrication and characterization of plasmonic nanocone antennas for strong spontaneous emission enhancement - Hoffmann, Björn; Vassant, Simon; Chen, Xue-Wen; Götzinger, Stephan; Sandoghdar, Vahid; Christiansen, Silke (Nanotechnology, 2015)
Plasmonic antennas are attractive nanostructures for a large variety of studies ranging from fundamental aspects of light-matter interactions at the nanoscale to industry-relevant applications such as ultrasensitive sensing, enhanced absorption in solar cells or solar fuel generation. A particularly interesting feature of these antennas is that they can enhance the fluorescence properties of emitters. Theoretical calculations have shown that nanocone antennas provide ideal results, but a high degree of manufacturing precision and control is needed to reach optimal performance. In this study, we report on the fabrication of nanocones with base diameters and heights in the range of 100 nm with variable aspect ratios using focused ion beam milling of sputtered nano-crystalline gold layers. The controlled fabrication process allows us to obtain cones with tailored plasmon resonances. The measured plasmon spectra show very good agreement with finite-difference time-domain calculations. Theoretical investigations predict that these nanocones can enhance the spontaneous emission rate of a quantum emitter by several hundred times while keeping its quantum efficiency above 60%.
Keywords: focused ion beam; nanocone antenna; plasmon spectroscopy; plasmonics; radiative rate enhancement

Grain Dependent Growth of Bright Quantum Emitters in Hexagonal Boron Nitride - Mendelson, Noah; Morales-Inostroza, Luis; Li, Chi; Ritika, Ritika; Nguyen, Minh Anh Phan; Loyola-Echeverria, Jacqueline; Kim, Sejeong; Götzinger, Stephan; Toth, Milos; Aharonovich, Igor (Advanced Optical Materials, 2020)
Point defects in hexagonal boron nitride have emerged as a promising quantum light source due to their bright and photostable room temperature emission. In this work, the incorporation of quantum emitters during chemical vapor deposition growth on a nickel substrate is studied. Combining a range of characterization techniques, it is demonstrated that the incorporation of quantum emitters is limited to (001) oriented nickel grains. Such emitters display improved emission properties in terms of brightness and stability. These emitters are further utilized and integrated with a compact optical antenna enhancing light collection from the sources. The hybrid device yields average saturation count rates of approximate to 2.9 x 10(6) cps and an average photon purity of g((2))(0) approximate to 0.1. The results advance the understanding of single photon emitter incorporation during chemical vapor deposition growth and demonstrate a key step towards compact devices for achieving maximum collection efficiency.
CRIS-Team WoS Importer:2020-11-27

High-Resolution Cryogenic Spectroscopy of Single Molecules in Nanoprinted Crystals - Musavinezhad, Mohammad; Renger, Jan; Zirkelbach, Johannes; Utikal, Tobias; Hail, Claudio U.; Basché, Thomas; Poulikakos, Dimos; Götzinger, Stephan; Sandoghdar, Vahid (ACS nano, 2024)
We perform laser spectroscopy at liquid helium temperatures (T = 2 K) to investigate single dibenzoterrylene (DBT) molecules doped in anthracene crystals of nanoscopic height fabricated by electrohydrodynamic dripping. Using high-resolution fluorescence excitation spectroscopy, we show that zero-phonon lines of single molecules in printed nanocrystals are nearly as narrow as the Fourier-limited transitions observed for the same guest-host system in the bulk. Moreover, the spectral instabilities are comparable to or less than one line width. By recording super-resolution images of DBT molecules and varying the polarization of the excitation beam, we determine the dimensions of the printed crystals and the orientation of the crystals’ axes. Electrohydrodynamic printing of organic nano- and microcrystals is of interest for a series of applications, where controlled positioning of quantum emitters with narrow optical transitions is desirable.
CRIS-Team Scopus Importer:2024-07-26
Keywords: nanocrystal; nanoprinting; quantum emitter; single molecule; single-photon source; spectroscopy

High-resolution vibronic spectroscopy of a single molecule embedded in a crystal - Zirkelbach, Johannes; Mirzaei, Masoud; Deperasińska, Irena; Kozankiewicz, Boleslaw; Gurlek, Burak; Shkarin, Alexey; Utikal, Tobias; Götzinger, Stephan; Sandoghdar, Vahid (Journal of Chemical Physics, 2022)
Vibrational levels of the electronic ground states in dye molecules have not been previously explored at a high resolution in solid matrices. We present new spectroscopic measurements on single polycyclic aromatic molecules of dibenzoterrylene embedded in an organic crystal made of para-dichlorobenzene. To do this, we use narrow-band continuous-wave lasers and combine spectroscopy methods based on fluorescence excitation and stimulated emission depletion to assess individual vibrational linewidths in the electronic ground state at a resolution of ∼30 MHz dictated by the linewidth of the electronic excited state. In this fashion, we identify several exceptionally narrow vibronic levels with linewidths down to values around 2 GHz. Additionally, we sample the distribution of vibronic wavenumbers, relaxation rates, and Franck-Condon factors, in both the electronic ground and excited states for a handful of individual molecules. We discuss various noteworthy experimental findings and compare them with the outcome of density functional theory calculations. The highly detailed vibronic spectra obtained in our work pave the way for studying the nanoscopic local environment of single molecules. The approach also provides an improved understanding of the vibrational relaxation mechanisms in the electronic ground state, which may help create long-lived vibrational states for applications in quantum technology.
CRIS-Team Scopus Importer:2022-04-01

Intensity squeezed light from a single emitter - Götzinger, Stephan; Chu, Xiao Liu; Sandoghdar, Vahid (Optics InfoBase Conference Papers, 2017)
We demonstrate a sub-shot noise single-emitter quantum light source, which uses a metallo-dielectric antenna for near-unity photon collection to obtain the most regular stream of single photons reported to date.
CRIS-Team Scopus Importer:2023-03-27

Nanoscopic Charge Fluctuations in a Gallium Phosphide Waveguide Measured by Single Molecules - Shkarin, Alexey; Rattenbacher, Dominik; Renger, Jan; Hönl, Simon; Utikal, Tobias; Seidler, Paul; Götzinger, Stephan; Sandoghdar, Vahid (Physical Review Letters, 2021)
We present efficient evanescent coupling of single organic molecules to a gallium phosphide (GaP) subwavelength waveguide (nanoguide) decorated with microelectrodes. By monitoring their Stark shifts, we reveal that the coupled molecules experience fluctuating electric fields. We analyze the spectral dynamics of different molecules over a large range of optical powers in the nanoguide to show that these fluctuations are light-induced and local. A simple model is developed to explain our observations based on the optical activation of charges at an estimated mean density of 2.5×1022 m-3 in the GaP nanostructure. Our work showcases the potential of organic molecules as nanoscopic sensors of the electric charge as well as the use of GaP nanostructures for integrated quantum photonics.
CRIS-Team Scopus Importer:2021-04-30

On Quantum Efficiency Measurements and Plasmonic Antennas - Matsuzaki, Korenobu; Liu, Hsuan Wei; Götzinger, Stephan; Sandoghdar, Vahid (ACS Photonics, 2021)
Quantum efficiency is a key quantity that describes the performance of light-emitting materials and is, thus, an important metric for assessing novel nanophotonic systems. This Perspective provides a concise discussion of the difficulties encountered in the characterization of quantum efficiencies, especially for studies that involve single emitters. In particular, we review various approaches that have been recently used for determining quantum efficiencies of emitters coupled to plasmonic antennas and highlight the subtleties and challenges that hinder precise measurements.
CRIS-Team Scopus Importer:2021-06-25
Keywords: antenna; plasmonic; Purcell enhancement; quantum efficiency; quenching; spontaneous emission

Organic Molecules as Origin of Visible-Range Single Photon Emission from Hexagonal Boron Nitride and Mica - Neumann, Michael; Wei, Xu; Morales-Inostroza, Luis; Song, Seunghyun; Lee, Sung Gyu; Watanabe, Kenji; Taniguchi, Takashi; Götzinger, Stephan; Lee, Young Hee (ACS nano, 2023)
The discovery of room-temperature single-photon emitters (SPEs) hosted by two-dimensional hexagonal boron nitride (2D hBN) has sparked intense research interest. Although emitters in the vicinity of 2 eV have been studied extensively, their microscopic identity has remained elusive. The discussion of this class of SPEs has centered on point defects in the hBN crystal lattice, but none of the candidate defect structures have been able to capture the great heterogeneity in emitter properties that is observed experimentally. Employing a widely used sample preparation protocol but disentangling several confounding factors, we demonstrate conclusively that heterogeneous single-photon emission at ∼2 eV associated with hBN originates from organic molecules, presumably aromatic fluorophores. The appearance of those SPEs depends critically on the presence of organic processing residues during sample preparation, and emitters formed during heat treatment are not located within the hBN crystal as previously thought, but at the hBN/substrate interface. We further demonstrate that the same class of SPEs can be observed in a different 2D insulator, fluorophlogopite mica.
CRIS-Team Scopus Importer:2023-07-07
Keywords: fluorophlogopite mica; hexagonal boron nitride; organic processing residue; polycyclic aromatic hydrocarbons; single photon emission

Partial Cloaking of a Gold Particle by a Single Molecule - Zirkelbach, Johannes; Gmeiner, Benjamin; Renger, Jan; Tuerschmann, Pierre; Utikal, Tobias; Götzinger, Stephan; Sandoghdar, Vahid (Physical Review Letters, 2020)
Extinction of light by material particles stems from losses incurred by absorption or scattering. The extinction cross section is usually treated as an additive quantity, leading to the exponential laws that govern the macroscopic attenuation of light. In this Letter, we demonstrate that the extinction cross section of a large gold nanoparticle can be substantially reduced-i.e., the particle becomes more transparent-if a single molecule is placed in its near field. This partial cloaking effect results from a coherent plasmonic interaction between the molecule and the nanoparticle, whereby each of them acts as a nanoantenna to modify the radiative properties of the other.
CRIS-Team WoS Importer:2020-09-18

Quantum Efficiency of Single Dibenzoterrylene Molecules in p-Dichlorobenzene at Cryogenic Temperatures - Musavinezhad, Mohammad; Shkarin, Alexey; Rattenbacher, Dominik; Renger, Jan; Utikal, Tobias; Götzinger, Stephan; Sandoghdar, Vahid (Journal of Physical Chemistry B, 2023)
We measure the quantum efficiency (QE) of individual dibenzoterrylene (DBT) molecules embedded in p-dichlorobenzene at cryogenic temperatures. To achieve this, we combine two distinct methods based on the maximal photon emission and on the power required to saturate the zero-phonon line to compensate for uncertainties in some key system parameters. We find that the outcomes of the two approaches are in good agreement for reasonable values of the parameters involved, reporting a large fraction of molecules with QE values above 50%, with some exceeding 70%. Furthermore, we observe no correlation between the observed lower bound on the QE and the lifetime of the molecule, suggesting that most of the molecules have a QE exceeding the established lower bound. This confirms the suitability of DBT for quantum optics experiments. In light of previous reports of low QE values at ambient conditions, our results hint at the possibility of a strong temperature dependence of the QE.
CRIS-Team Scopus Importer:2023-07-21

Robust Tipless Positioning Device for Near-Field Investigations: Press and Roll Scan (PROscan) - Liu, Hsuan-Wei; Becker, Michael A.; Matsuzaki, Korenobu; Kumar, Randhir; Götzinger, Stephan; Sandoghdar, Vahid (ACS nano, 2022)
Scanning probe microscopes scan and manipulate a sharp tip in the immediate vicinity of a sample surface. The limited bandwidth of the feedback mechanism used for stabilizing the separation between the tip and the sample makes the fragile nanoscopic tip very susceptible to mechanical instabilities. We propose, demonstrate, and characterize an alternative device based on bulging a thin substrate against a second substrate and rolling them with respect to each other. We showcase the power of this method by placing gold nanoparticles and semiconductor quantum dots on the two opposite substrates and positioning them with nanometer precision to enhance the fluorescence intensity and emission rate. Furthermore, we exhibit the passive mechanical stability of the system over more than 1 h. Our design concept finds applications in a variety of other scientific and technological contexts, where nanoscopic features have to be positioned and kept near contact with each other.
CRIS-Team WoS Importer:2022-08-26

Sensing nanoparticles with a cantilever-based scannable optical cavity of low finesse and sub- λ3 volume - Kelkar, Hrishikesh; Wang, Daqing; Martin-Cano, Diego; Hoffmann, Björn; Christiansen, Silke; Götzinger, Stephan; Sandoghdar, Vahid (Physical Review Applied, 2015)
We report on the realization of an open plane-concave Fabry-Perot resonator with a mode volume below λ3 at optical frequencies. We discuss some of the less-common features of this microcavity regime and show that the ultrasmall mode volume allows us to detect cavity resonance shifts induced by single nanoparticles even at quality factors as low as 100. Being based on low-reflectivity micromirrors fabricated on a silicon cantilever, our experimental arrangement provides broadband operation, tunability of the cavity resonance, and lateral scanning. These features are interesting for a range of applications including biochemical sensing, modification of photophysics, and optomechanical studies.

Single-Molecule Vacuum Rabi Splitting: Four-Wave Mixing and Optical Switching at the Single-Photon Level - Pscherer, André; Meierhofer, Manuel; Wang, Daqing; Kelkar, Hrishikesh; Martín-Cano, Diego; Utikal, Tobias; Götzinger, Stephan; Sandoghdar, Vahid (Physical Review Letters, 2021)
A single quantum emitter can possess a very strong intrinsic nonlinearity, but its overall promise for nonlinear effects is hampered by the challenge of efficient coupling to incident photons. Common nonlinear optical materials, on the other hand, are easy to couple to but are bulky, imposing a severe limitation on the miniaturization of photonic systems. In this Letter, we show that a single organic molecule acts as an extremely efficient nonlinear optical element in the strong coupling regime of cavity quantum electrodynamics. We report on single-photon sensitivity in nonlinear signal generation and all-optical switching. Our work promotes the use of molecules for applications such as integrated photonic circuits operating at very low powers.
CRIS-Team Scopus Importer:2021-10-08

Single photon sources for quantum radiometry: a brief review about the current state-of-the-art - Kueck, Stefan; Lopez, Marco; Hofer, Helmuth; Georgieva, Hristina; Christinck, Justus; Rodiek, Beatrice; Porrovecchio, Geiland; Smid, Marek; Götzinger, Stephan; Becher, Christoph; Fuchs, Philipp; Lombardi, Pietro; et al. (Applied Physics B-Lasers and Optics, 2022)
Single-photon sources have a variety of applications. One of these is quantum radiometry, which is reported on in this paper in the form of an overview, specifically of the current state of the art in the application of deterministic single photon sources to the calibration of single photon detectors. To optimize single-photon sources for this purpose, extensive research is currently carried out at the European National Metrology Institutes (NMIs), in collaboration with partners from universities. Single-photon sources of different types are currently under investigation, including sources based on defect centres in (nano-)diamonds, on molecules and on semiconductor quantum dots. We will present, summarise, and compare the current results obtained at European NMIs for single-photon sources in terms of photon flux, single-photon purity, and spectral power distribution as well as the results of single-photon detector calibrations carried out with this type of light sources.
CRIS-Team Scopus Importer:2022-02-04

Small slot waveguide rings for on-chip quantum optical circuits - Rotenberg, Nir; Tuerschmann, Pierre; Haakh, Harald R.; Martin-Cano, Diego; Götzinger, Stephan; Sandoghdar, Vahid (Optics Express, 2017)
Nanophotonic interfaces between single emitters and light promise to enable new quantum optical technologies. Here, we use a combination of finite element simulations and analytic quantum theory to investigate the interaction of various quantum emitters with slot-waveguide rings. We predict that for rings with radii as small as 1.44 μm, with a Q-factor of 27,900, near-unity emitter-waveguide coupling efficiencies and emission enhancements on the order of 1300 can be achieved. By tuning the ring geometry or introducing losses, we show that realistic emitter-ring systems can be made to be either weakly or strongly coupled, so that we can observe Rabi oscillations in the decay dynamics even for micron-sized rings. Moreover, we demonstrate that slot waveguide rings can be used to directionally couple emission, again with near-unity efficiency. Our results pave the way for integrated solid-state quantum circuits involving various emitters.
CRIS-Team Scopus Importer:2023-03-27

Spectral splitting of a stimulated Raman transition in a single molecule - Zirkelbach, Johannes; Gurlek, Burak; Mirzaei, Masoud; Shkarin, Alexey; Utikal, Tobias; Götzinger, Stephan; Sandoghdar, Vahid (Physical Review Research, 2023)
The small cross-section of Raman scattering poses a great challenge for its direct study at the single-molecule level. By exploiting the high Franck-Condon factor of a common-mode resonance, choosing a large vibrational frequency difference in electronic ground and excited states and operating at T<2K, we succeed at driving a coherent stimulated Raman transition in individual molecules. We observe and model a spectral splitting that serves as a characteristic signature of the phenomenon at hand. Our study sets the ground for exploiting the intrinsic optomechanical degrees of freedom of molecules for applications in solid-state quantum optics and information processing.
CRIS-Team Scopus Importer:2024-12-16

Strong biexciton emission enhancement of a single quantum dot by a plasmonic nanocone antenna - Matsuzaki, Korenobu; Liu, Hsuan Wei; Dutschke, Anke; Götzinger, Stephan; Sandoghdar, Vahid (Optics InfoBase Conference Papers, 2017)
CRIS-Team Scopus Importer:2023-03-27

Strong plasmonic enhancement of biexciton emission: Controlled coupling of a single quantum dot to a gold nanocone antenna - Matsuzaki, Korenobu; Vassant, Simon; Liu, Hsuan-Wei; Dutschke, Anke; Hoffmann, Björn; Chen, Xuewen; Christiansen, Silke; Buck, Matthew R.; Hollingsworth, Jennifer A.; Götzinger, Stephan; Sandoghdar, Vahid (Scientific Reports, 2017)
Multiexcitonic transitions and emission of several photons per excitation comprise a very attractive feature of semiconductor quantum dots for optoelectronics applications. However, these higher-order radiative processes are usually quenched in colloidal quantum dots by Auger and other nonradiative decay channels. To increase the multiexcitonic quantum efficiency, several groups have explored plasmonic enhancement, so far with moderate results. By controlled positioning of individual quantum dots in the near field of gold nanocone antennas, we enhance the radiative decay rates of monoexcitons and biexcitons by 109 and 100 folds at quantum efficiencies of 60 and 70%, respectively, in very good agreement with the outcome of numerical calculations. We discuss the implications of our work for future fundamental and applied research in nano-optics.

Thermal origin of light emission in nonresonant and resonant nanojunctions - Ott, Christian; Götzinger, Stephan; Weber, Heiko B. (Physical Review Research, 2020)
Electron tunneling is associated with light emission. In order to elucidate its generating mechanism, we provide an experimental ansatz that employs fixed-distance epitaxial graphene as metallic electrodes. In contrast to previous experiments, this open geometry permits an unobscured light spread from the tunnel junction, enabling both a reliable calibration of the visible to infrared emission spectrum and a detailed analysis of the dependence of the parameters involved. In a nonresonant geometry, the emitted light is perfectly characterized by a Planck spectrum. In an electromagnetically resonant environment, resonant radiation is added to the thermal spectrum, both being strictly proportional in intensity. In full agreement with a simple heat conduction model, we provide evidence that in both cases the light emission stems from a hot electronic subsystem in interaction with its linear electromagnetic environment. In a long-running discussion whether the light is of thermal or electromagnetic origin, these results on graphene nanojunctions clearly favor the thermal pictur

Truncated Metallo-Dielectric Omnidirectional Reflector: Collecting Single Photons in the Fundamental Gaussian Mode with 95% Efficiency - Li, Wancong; Morales Inostroza, Luis; Xu, Weiwang; Zhang, Pu; Renger, Jan; Götzinger, Stephan; Chen, Xue-Wen (ACS Photonics, 2020)
We propose a novel antenna structure that funnels single photons from a single emitter with unprecedented efficiency into a low-divergence fundamental Gaussian mode. Our device relies on the concept of creating an omnidirectional photonic bandgap to inhibit unwanted large-angle emission and to enhance small-angle defect-guided-mode emission. The new photon collection strategy is intuitively illustrated, rigorously verified, and optimized by implementing an efficient, body-of-revolution, finite-difference, time-domain method for in-plane dipole emitters. We investigate a few antenna designs to cover various boundary conditions posed by fabrication processes or material restrictions and theoretically demonstrate that collection efficiencies into the fundamental Gaussian mode exceeding 95% are achievable. Our antennas are broadband, insensitive to fabrication imperfections and compatible with a variety of solid-state emitters such as organic molecules, quantum dots, and defect centers in diamond. Unidirectional and low-divergence Gaussian-mode emission from a single emitter may enable the realization of a variety of photonic quantum computer architectures as well as highly efficient lightmatter interfaces.
CRIS-Team WoS Importer:2020-10-16

Turning a molecule into a coherent two-level quantum system - Wang, Daqing; Kelkar, Hrishikesh; Martin-Cano, Diego; Rattenbacher, Dominik; Shkarin, Alexey; Utikal, Tobias; Götzinger, Stephan; Sandoghdar, Vahid (Nature Physics, 2019)
The use of molecules in quantum optical applications has been hampered by incoherent internal vibrations and other phononic interactions with their environment. Here we show that an organic molecule placed into an optical microcavity behaves as a coherent two-level quantum system. This allows the observation of 99% extinction of a laser beam by a single molecule, saturation with less than 0.5 photons and non-classical generation of few-photons super-bunched light. Furthermore, we demonstrate efficient interaction of the molecule–microcavity system with single photons generated by a second molecule in a distant laboratory. Our achievements represent an important step towards linear and nonlinear quantum photonic circuits based on organic platforms.
CRIS-Team Scopus Importer:2019-05-17

Turning an organic molecule into a coherent two-level quantum system using a tunable fabry-perot microcavity - Wang, Daqing; Kelkar, Hrishikesh; Martin-Cano, Diego; Rattenbacher, Dominik; Shkarin, Alexey; Utikal, Tobias; Götzinger, Stephan; Sandoghdar, Vahid (Optics InfoBase Conference Papers, 2019)
By coupling an organic molecule to a Fabry-Perot microcavity, we turn it into a coherent two-level quantum system. We further demonstrate efficient interaction of this system with single photons generated by a second molecule.
CRIS-Team Scopus Importer:2019-07-09